Host-guest properties of the trinuclear arene-ruthenium cluster cation [H3Ru3(C6H6)(C6Me6)2(O)]+ - Therrien, Bruno; Vieille-Petit, Ludovic; Süss-Fink, Georg (My University, 2004)
The trinuclear arene-ruthenium cluster cation [H3Ru3(C6H6)(C6Me6)2(O)]+, contg. a ?3-oxo cap and three arene ligands that span a hydrophobic pocket above the metal skeleton, has been crystd. as tetrafluoroborate salt in the presence of various guest mols. The host-guest complexes have been characterized by single-crystal x-ray structure anal. With chloroform as the guest mol., a CHCl3 mol. sits perfectly in the hydrophobic pocket, the hydrogen atom being encapsulated inside the cavity. When dioxane is added during the crystn. process, the cluster forms infinite chains which are connected by a complex network of hydrogen bonds involving the ?3-oxo ligand, water and dioxane mols. Interestingly, in the presence of phenol, a water mol. is hydrogen-bonded between the ?3-oxo ligand and the phenol mol., forming a one-dimensional ?3-O ··· H2O ··· HO hydrogen-bonded chain. Finally, with benzoic acid, a head-to-tail host-guest chain is obtained, the Ph ring being incorporated in the hydrophobic pocket, while the acid group is hydrogen-bonded to the ?3-oxo ligand. [on SciFinder(R)]
Keywords: host guest property trinuclear benzene pentamethylcyclopentadienyl ruthenium hydride oxo; pentamethylcyclopentadienylruthenium benzene oxo hydride cluster cation host guest complex; crystal mol structure pentamethylcyclopentadienylruthenium benzene oxo hydride host guest